Pengelolaan Laba dalam Sektor Consumer Non-Cyclicals: Peran Aset Pajak Tangguhan, Skala Perusahaan, dan Leverage di Bursa Efek Indonesia - Safitri, Yulia; Purwatiningsih, Purwatiningsih (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research aims to empirically prove the influence of deferred tax assets, company size and leverage on earnings management. This research was conducted at a Consumer Non-Cyclical sector company. The research method used is quantitative. The type of data used is secondary in the form of annual financial reports published on the Indonesia Stock Exchange (BEI) for 2018-2022. Samples were collected using purposive sampling. The number of companies used as research samples was 28 companies with a research period of 5 (five) years, so that 140 observation data were obtained. Data processing uses the Eviews 12 Statistical Program by collecting related data then analyzing descriptive statistics of regression model estimates, model suitability tests, classical assumption tests, coefficient of determination (R 2) panel data regression analysis, F statistical tests and t statistical tests, Results The t statistical test for the variable deferred tax assets partially influences earnings management, but company size and leverage partially have no influence on earnings management. F test results: Deferred tax assets, company size and leverage simultaneously influence earnings management.